1-Aminocyclopropane-1-Carboxylic Acid Concentrations in Shoot-Forming and Non-Shoot-Forming Tobacco Callus Cultures - Grady, Karen Lee (1982)
Shoot-forming tobacco (Nicotiana tabacum var. Wisconsin 38) callus tissues contain significantly lower concentrations of the ethylene precursor 1-aminocyclopropane-1-carboxylic acid compared to non-shoot-forming callus tissues. This difference is evident 1 day after subculture to shoot-forming or non-shoot-forming medium, and is maintained through the first week of growth. The lack of auxin in shoot-forming medium is the probable cause for this difference in ACC concentrations.